Binding Specificity of Radiolabeled Cyclic Peptide 153Sm-DTPA-c(CGRRAGGSC) to MHCC97-H Human Liver Cancer Cells and its Antitumor Effects in vivo. (December 2016) - Wu, Qinghua; He, Yujie; Gu, Chen; Jiang, Jianwei; Zhou, Huan; Zhou, Shi
Objective: This objective of this study is to investigate the effects of the radiolabeled cyclic peptide 153 Sm-DTPA-c(CGRRAGGSC) on MHCC97-H human liver cancer cells in vitro and in vivo . Methods: The protein expression levels were examined by Western blot analysis. Biological activity of 153 Sm-DTPA-c(CGRRAGGSC) was assessed with the radioligand binding assay and competitive inhibition experiment. Subcellular localization of the cyclic peptide was observed by fluorescence microscopy. Animals were implanted with MHCC97-H cells and administered with 153 Sm-DTPA-c(CGRRAGGSC). Hematoxylin and eosin staining, electron microscopy, and immunohistochemistry were performed to evaluate the effects of 153 Sm-DTPA-c(CGRRAGGSC) on implanted tumors. Result: The expression levels of interleukin 11 receptor were significantly elevated, by 2-to 5-fold, in tumor cell lines, especially for MHCC97-H cells. Characterization of 153 Sm-DTPA-c(CGRRAGGSC) showed that the biological activity of the cyclic peptide was not altered after labeling, and the radiolabeled cyclic peptide exhibited sufficient binding affinity to interleukin 11 receptor . The cyclic peptide of c(CGRRAGGSC) was mainly distributed in the cytoplasm and on the cell membrane of MHCC97-H cells. The in vivo experiments showed that the tumor growth was significantly inhibited by the treatment of 153 Sm-DTPA-c(CGRRAGGSC). The inhibitory effect of 153 Sm-DTPA-c(CGRRAGGSC) on tumor growth was further confirmed by Hematoxylin and eosin staining, electron microscopy, and immunohistochemistry. Moreover, the expression levels of interleukin 11 receptor in implanted tumors were significantly decreased in the treatment groups. Conclusion: 153 Sm-DTPA-c (CGRRAGGSC) could specifically bind to interleukin 11 receptor on MHCC97-H liver tumor cells, inhibiting the cell proliferation and inducing cellular apoptosis. These findings provide experimental evidence for the development of individual treatment of liver cancers, as well as recurrence and metastasis.